(3TQM GdebOeI GdCRgQjI aj Yde GdYQHjIs - (3GdLQLGhj GdCRgQj GdeUQj, Rjf GdOjf, GdhbGO, NGdO Hf YHO Gddg Hf CHj HcQ, J (B905 (3g`s ((3eMeO Hf MSjfs)
(3ChdgG (B:s
(3GdMeO ddg Ydi LejY GdCMhGdhHYO ajbhd NGdO Hf YHO Gddg GdCRgQj bO SCdfj Cf CTQM ebOeJj GdCRgQjI aj Yde GdYQHjIaCLHJg Edi Pdcs
(3BNQgG (B:s
(3hGdfGS eYWha Ydi GdLfI haj gPG GdbOQ caGjI ddeHJOF hGdMeO ddg QH GdYGdejfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 2 / 297s
(3eYLe GdeDdajf(B: 8 / 26s
(3cTa GdXfhf(B: 2 / 1798s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdfMhs